Metabolic and Pancreatic Derangement in type 2 Diabetic Rat - Noordin, Liza; Muhamad Nor, Nor Asiah; Abu Bakar , Nor Hidayah; Wan Ahmad, Wan Amir Nizam (IIUM Medical Journal Malaysia, 2021)
Introduction: The prevalence of diabetes mellitus is increasing globally, despite the best current therapies available. A large diversity of animal models has been developed for better understanding the pathogenesis of diabetes mellitus. This study aimed to develop a rat model that mimics the metabolic characteristics of human type 2 diabetes mellitus. Methods: Twenty-four male Sprague–Dawley rats (200–250 g) were divided into two groups and fed either a commercially available standard pellet diet (n=8) or a self-prepared high-fat diet (HFD) (n=16) for 6 weeks. HFD-fed rats were significantly obese compared to standard-fed rats. Eight of the obese rats were injected a single low dose of streptozotocin (STZ) at 35 mg/kg intraperitoneally to induce type 2 diabetic rat (T2DR) and were monitored for 6 weeks. Results: The weekly fasting blood glucose levels (FBG) in T2DR remained consistently high throughout the 6 weeks. The T2DR group exhibits decreased body weight, increased water intake, increased 24-hour urine volume with microalbuminuria, hyperlipidemia, altered liver and kidney functions, and structural changes of the islet of Langerhans. Conclusion: This model simulates the natural disease progression and metabolic characteristics of type 2 diabetic patients. This model mimics the human syndrome that can be maintained at a reasonable cost, and easy to develop.